Impact of Encapsulated Thyme, Clove, and Sage Essential Oils on the Antioxidant, Physicochemical, DNA Binding, and Cleaving Properties of Chewing Gum - Barman, Busra; Budama-Kilinc, Yasemin; Kutlu, Gozde; Karimidastjerd, Atefeh; Khiabani, Arezou Habibzadeh; Gok, Bahar; Basyigit, Bulent; Palabiyik, Ibrahim; Konar, Nevzat; Tornuk, Fatih; Toker, Omer Said (AMER CHEMICAL SOC, 2025)
The use of essential oils (EOs) in various food matrices has gained interest due to their olfactory properties, as well as their antimicrobial and antioxidant activities, making them valuable in the development of functional foods. In this study, thyme, clove, and sage EOs were nanoencapsulated using the ionic gelation method. Their encapsulation efficiency, DNA binding and cleavage properties, particle size, and zeta potential were evaluated. These encapsulated EOs were then incorporated into sugar-free chewing gum formulations, and their antioxidant, anticarcinogenic, sensory, textural, and color properties were analyzed. The results showed the highest encapsulation efficiency for thyme EO (61.51% +/- 1.52), followed by clove (56.10% +/- 1.87) and sage (52.59% +/- 0.56). The average particle sizes (Z-average) of encapsulated thyme, clove, and sage EOs were 330.1 +/- 10.89, 452.6 +/- 5.52, and 553.7 +/- 0.01 d nm, respectively. All encapsulated EOs possessed negative zeta potential values ranging from -26.40 to -32.30 mV and polydispersity index (PDI) values between 0.399 and 0.433. The antioxidant activity of chewing gums increased with the addition of nanocapsules, and the percentage of DPPH inhibited the lowest for control with 6.73% +/- 0.32 and 40.41% +/- 0.07 for thyme in sugar-free gums. The concentrations of 0.05, 0.1, and 0.2% (w/w) were applied to evaluate the hydrolytic and oxidative cleavage activities. The DNA cleavage experiment revealed that chewing gum samples containing sage EO exhibited hydrolytic and oxidative cleavage activities. In contrast, chewing gum samples containing clove and thyme EOs exhibited only hydrolytic cleavage activity. The addition of 0.2% (w/w) of encapsulated thyme, clove, and sage EOs did not negatively affect the sensory and textural properties of the gum samples. Ultimately, the findings demonstrate that the incorporation of encapsulated EOs successfully enhanced the antioxidant properties of sugar-free gum without compromising its sensory quality.
Keywords: IN-VITRO; MICROENCAPSULATION; CYCLODEXTRINS; OFFICINALIS; LIPOSOMES; Chemistry